Martyrs and Madonnas: Inácio de Azevedo, the Brazil Martyrs, and the Global Circulation of the Madonna of Santa Maria Maggiore - Paul Nelles (Religions, 2023)
The article offers a revisionist account of the early circulation of copies of the Madonna of Santa Maria Maggiore, known since the nineteenth century as the Salus Populi Romani. Traditionally, the propulsion of the image into global circulation has been attributed variously to Pius V or Francisco Borja, the third Superior General of the Society of Jesus. The article argues that the circulation of the Saint Luke Madonna, as it was known at the time, was closely tied to the martyr’s cult that grew up around the Jesuit missionary Inácio de Azevedo and the so-called Brazil Martyrs, a group of Jesuits murdered by Calvinist corsairs off the Canary Islands in 1570. Azevedo had intended to carry a copy of the Roman icon to Brazil, a copy that perished at sea with Azevedo and the party of Jesuit missionaries. The article suggests that the popularity of the image among Jesuits in Europe and the overseas missions was fueled by the nascent martyr’s cult that followed Azevedo’s death. Painted copies of the Saint Luke Madonna came to function, together with relics of the Eleven Thousand Virgins of Cologne, as proxies for the missing material remains of the martyred Jesuits. The article argues that while the distribution of the image was globally extensive, circulation was restricted to an internal Jesuit martyr’s cult.